Parate Executie: In the Context of Principle of Proportionality and the Principle of Speedy Administration of Justice - Ni Putu Paramita Dewi (Prosiding Seminar Hukum Aktual Fakultas Hukum Universitas Islam Indonesia, 2025)
Parate execution is a legal privilege granted to documents that are equivalent to court judgments, such as mortgage and fiduciary rights. However, with the existence of a judicial review through the Constitutional Court Decision 18/PUU-XVII/2019, there are juridical implications regarding the position of Parate execution. This review specifically focuses on Article 15, Paragraph (2) and Paragraph (3) of Law Number 42 of 1999 concerning Fiduciary Guarantees. On one hand, Parate execution can achieve proportionality by balancing the interests of both parties through the inclusion of a default clause before execution by the creditor. It also ensures equal treatment of documents equivalent to court judgments by following civil procedure law procedures. On the other hand, this may result in additional procedures that do not require court approval, potentially hindering the principle of speedy justice administration.Keywords: Parate Executie, Fiduciary Law, Mortgage Law, Executie, Speedy Administration of Justice